Leveraging Health Care Communication Channels for Environmental Health Outreach in New Jersey. Issue 6 (November 2020) - Flanagan, Sara V.; Braman, Stuart; Puelle, Rose; Gleason, Jessie A.; Spayd, Steven E.; Procopio, Nicholas A.; Prosswimmer, Geralyn; Navas-Acien, Ana; Graziano, Joseph; Chillrud, Steve
Abstract : Households with pregnancies and young children are a priority group for outreach on private well water screening due to the widespread occurrence and toxicity of common groundwater contaminants such as arsenic. Given the trusted role of health care providers as communicators of health risk, Columbia University investigators and New Jersey government partners collaborated with Hunterdon Healthcare to offer free well testing to residents of Hunterdon County, a hot spot for naturally occurring arsenic in New Jersey. Through practice-based test kit distribution and online patient portal messages, supported by a public multimedia campaign, we tested 433 private wells and alerted 50 families about elevated arsenic found in their drinking water. These health care–facilitated outreach strategies allowed for targeting based on geographic and demographic risk and suggested opportunities to better leverage communication channels, such as incorporating questions on home water source into the electronic medical record. Abstract : Supplemental Digital Content is Available in the Text.